2017
DOI: 10.1021/acs.jpcc.6b12864
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, Optical, and Mechanical Properties of Diamond Nanowires Encapsulated in Carbon Nanotubes: A First-Principles View

Abstract: In recent years, carbon-based complex nanostructures have been explored due to many of their unique properties and related applications. Here we employ theoretical simulation based on density functional theory to investigate electronic, optical, and mechanical properties of a new type of the carbon-based complex nanostructure, i.e., experimentally fabricated one-dimensional complex material of hydrogenated diamond nanowires encapsulated in carbon nanotubes (CNW@CNT). The complex structure CNW@CNT is found to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…49 In another study, Wang et al reported a distortion in the structure of CNTs with the encapsulation of carbon nanowires. 14 Unlike in indigo@ (6,6)CNT, in all other complexes indigo was found to be slightly tilted with respect to the tube-axis, keeping the geometric centres of indigo and the CNT coincident with each other. Compared to indigo@(7,7)CNT, in indigo@(8,8)CNT, a larger inclination for indigo with respect to the tube-axis was observed so as to bring the distance between the phenyl groups of indigo and the (8,8)CNT into the range of p-p stacking.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…49 In another study, Wang et al reported a distortion in the structure of CNTs with the encapsulation of carbon nanowires. 14 Unlike in indigo@ (6,6)CNT, in all other complexes indigo was found to be slightly tilted with respect to the tube-axis, keeping the geometric centres of indigo and the CNT coincident with each other. Compared to indigo@(7,7)CNT, in indigo@(8,8)CNT, a larger inclination for indigo with respect to the tube-axis was observed so as to bring the distance between the phenyl groups of indigo and the (8,8)CNT into the range of p-p stacking.…”
Section: Resultsmentioning
confidence: 82%
“…The endohedral complexes of carbon nanotubes with organic molecules are mainly stabilized by the p-p and X-HÁ Á Áp (X = C, N, and O) interactions. The importance of p-p interactions in the complexes such as oligothiophene@CNT, 10,11 pioglitazone@ CNT, 12 acetone@CNT 13 and diamond nanowire@CNT 14 was elucidated using theoretical and experimental methods. The above studies report that the attractive interactions between the p-conjugated CNT and the encapsulated moiety impart stability to these complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation